KONSEP DASAR TEORI PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI MENURUT JEAN PIAGET - Novia Istiqomah; Maemonah Maemonah (Khazanah Pendidikan, 2021)
There are many theories about human development, one of which is Jean Piaget's theory of development, this theory will be discussed by researchers how the Basic Concepts of Cognitive Development in Early Childhood According to Jean Piaget. Studying the theory of cognitive development will be the basis for understanding every step of cognitive development, especially in early childhood. Piage describes the concepts used in children's cognitive processes and how the stages of cognitive development in children are. This time the research was conducted through the library method which is a method of searching, collecting and analyzing data sources in books, scientific articles and scientific sources.